2013
DOI: 10.1037/a0032864
|View full text |Cite
|
Sign up to set email alerts
|

Coparenting moderates the association between firstborn children’s temperament and problem behavior across the transition to siblinghood.

Abstract: The contribution of individual (i.e., negative reactivity) and environmental (i.e., coparenting) characteristics in predicting firstborns’ adjustment after a sibling's birth were examined. Mothers, fathers, and firstborn children from 241 families participated in a family freeplay to assess coparenting interactions before the birth of the second child and parents completed questionnaires on children's temperamental characteristics and behavior problems. Children's externalizing problems significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 66 publications
(115 reference statements)
6
57
1
Order By: Relevance
“…Although many studies have examined cooperative and undermining coparenting separately and found that they show different child and family level correlates (e.g., Laxman et al, 2013), most have not examined the interaction between the two. A recent study by Kolak and Volling (2013), however, found that cooperative coparenting moderated the effect of undermining coparenting in predicting children’s externalizing problems after the birth of a sibling. Specifically, cooperative coparenting was a protective factor for negatively reactive children in families where parents engaged in high levels of undermining coparenting; children showed increases in externalizing behaviors after the birth of a sibling only when their parents engaged in high undermining coparenting and low cooperative coparenting.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Although many studies have examined cooperative and undermining coparenting separately and found that they show different child and family level correlates (e.g., Laxman et al, 2013), most have not examined the interaction between the two. A recent study by Kolak and Volling (2013), however, found that cooperative coparenting moderated the effect of undermining coparenting in predicting children’s externalizing problems after the birth of a sibling. Specifically, cooperative coparenting was a protective factor for negatively reactive children in families where parents engaged in high levels of undermining coparenting; children showed increases in externalizing behaviors after the birth of a sibling only when their parents engaged in high undermining coparenting and low cooperative coparenting.…”
mentioning
confidence: 87%
“…In addition to children’s temperamental characteristics, how well mothers and fathers support each other in parenting was important for children’s adjustment after the birth of a sibling (Kolak & Volling, 2013). Cooperative coparenting describes parents’ warmth and assistance of one another in their parenting efforts, whereas undermining coparenting is characterized by parents’ invalidation of each other’s efforts, disagreement with, and interruption of the other parent (Belsky, Putnam, & Crnic, 1996).…”
mentioning
confidence: 99%
“…Coparenting between mothers and fathers in the form of either supportive or conflictual relations also predicts externalizing and disruptive behaviors in young children (Belsky, Woodworth, & Crnic, 1996; Schoppe-Sullivan et al, 2009). We have also found that home observations of coparenting (low support and undermining) between parents during triadic interaction with the firstborn before the birth predicted increases in externalizing behaviors 1 month after the birth, and that supportive and undermining coparenting interacted so that the greatest increases in externalizing behavior problems occurred when mothers and fathers were high on undermining coparenting and low on supportive coparenting (Kolak & Volling, 2013). Parenting stress (Shaw et al, 2001) and the social support parents receive from family and friends may play a role in the emergence of disruptive behaviors, most likely due to the fact that reliance on others for emotional, financial, and instrumental support can alleviate much of the caregiving stress, reduce role overload and enhance parental mental health (Lee, Anderson, Horowitz, & August, 2009; Guralnick, Hammond, Neville, & Connor, 2008; Hoagwood et al, 2010; DeGarmo, Patras, & Eap, 2008; Leahy-Warren, McCarthy, & Corcoran, 2012).…”
Section: Risk and Protective Factors In The Prediction Of Early Aggrementioning
confidence: 58%
“…Most firstborn children enter siblinghood before age three, suggesting it may be more developmentally advantageous to direct intervention efforts to parents rather than children. Because earlier findings from this study suggested supportive coparenting predicted less problem behavior of children across the transition (Kolak & Volling, 2013), focusing on promoting positive relations between mothers and fathers as they make the transition may benefit the entire family.…”
Section: Resultsmentioning
confidence: 78%
“…Our results also suggested that alternative interventions might be needed in order assist families with the transition period and support children’s adjustment. Recent research examining the child and family factors that predicted children’s emotional and behavioral adjustment after the birth of a second child, strongly suggested that focusing on parental discipline and the management of children’s misbehaviors, as well as the coparenting relationship may be advantageous targets for pre-birth education classes or interventions (Volling et al, in press; Kolak & Volling, 2013; Song & Volling, 2015). Most firstborn children enter siblinghood before age three, suggesting it may be more developmentally advantageous to direct intervention efforts to parents rather than children.…”
Section: Resultsmentioning
confidence: 99%